2016
DOI: 10.1021/acscatal.6b01025
|View full text |Cite
|
Sign up to set email alerts
|

Monomolecular Cracking Rates of Light Alkanes over Zeolites Determined by IR Operando Spectroscopy

Abstract: The coverage of H-MFI zeolite acid sites by light alkanes (C3-C7) at monomolecular cracking reaction conditions was determined using infrared operando spectroscopy. At such conditions, alkane adsorption through H-bonding leads to a fully reversible perturbation of the zeolite νOH band at 3600 cm-1. This was used to assess the coverage at various temperatures and pressures, allowing for the determination of the adsorption thermodynamic parameters at reaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
87
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(105 citation statements)
references
References 50 publications
17
87
1
Order By: Relevance
“…[7,20,21,25] Af irst explanation accountingf or this discrepancy could lie in the harmonic approximation used to compute entropies as it is known to overestimate the contribution of low frequency modes. [24,33] The consideration of explicit models for the hydrogen bond couldi mprove the agreement with experiments. This might not correctly describe the hydrogen-bonded states for which the distance from the oxygen atom bearing the proton and the directionality of the H-bond has as ubstantial influence.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…[7,20,21,25] Af irst explanation accountingf or this discrepancy could lie in the harmonic approximation used to compute entropies as it is known to overestimate the contribution of low frequency modes. [24,33] The consideration of explicit models for the hydrogen bond couldi mprove the agreement with experiments. This might not correctly describe the hydrogen-bonded states for which the distance from the oxygen atom bearing the proton and the directionality of the H-bond has as ubstantial influence.…”
mentioning
confidence: 88%
“…[4,12,16,28] However,s tate of the art simu-lations predict as trong influence of temperature on the adsorptione ntropy, D ads S, [7,20,25,[29][30][31] which was assumed to be negligible in previous studies. [33] We presenth ere astudy on the influence of zeolite structure (FER, TON, MFI and CHA) on the monomolecular cracking of light alkanes( propane and n-butane). [20,29] Accountingf or such temperature effects, the latest studies combining molecular simulations and cracking rate measurements suggest that structure-activity trends are explained neither by the adsorption parameters, nor by activation entropy, but by changes in activation energies E a that would be affected by the alkane chain length, or the zeolitet opology.…”
mentioning
confidence: 99%
“…It is evident from these equations that to determine Δ H ≠ int and Δ S ≠ int at reaction temperatures (>673 K) it is necessary to first determine Δ H ads‐H+ and Δ S ads‐H at reaction temperatures. Until recently, this has not been attempted using experimental adsorption measurements because of the tendency of the alkane to relocate to siliceous parts of the framework at high temperature, and because of the occurrence of chemical reactions at temperatures above ≈600 K . Moreover, several theoretical studies have shown that the distribution of adsorbed alkanes within the pores of a zeolite changes with the adsorption temperature, and consequently any insights gleaned from low temperature adsorption experiments are unlikely to be transferrable to reaction temperatures .…”
Section: Experimental Studies Of Reaction At Brønsted Acid Sitesmentioning
confidence: 99%
“…Similar products can be formed during the treatment of n-hexane over H-ZSM-5 zeolite, but require a much higher reaction temperature of 593 K relative to that used for cyclopentadiene because of the high activation energy of n-alkane cracking (~200 kJ mol -1 ) [49,50]. It is likely that the substituted indenes and naphthalenes observed in the present study were formed from the secondary reaction of cyclopentadiene and cyclopentene.…”
Section: Catalytic Conversion Of Jp-10mentioning
confidence: 52%
“…These findings are shown in Table 1-5. Their findings were confirmed by Li et al [50], who simultaneously measured surface coverages and monomolecular cracking rates to directly determine intrinsic cracking rates and activation energies. …”
Section: Hydrocarbon Cracking Mechanismmentioning
confidence: 62%